Patterns of housing demand under uncertainty: a case study in Lisbon - Costa Pinto, Teresa (2013)
From the results of a questionnaire to the potential demand for housing in a residential area of Lisbon, we intend to explore in this paper, patterns of housing demand with taking into account the current context of crisis and uncertainty surrounding the housing markets and societal evolution itself. Therefore, the sociological profiles of potential buyers / tenants are presented, exploring the relationship of certain residential options (in terms of location, house type, tenure and price) and the particular characteristics of individuals who want change their residential situation: socio-economic group, age, stage of life course and location of current residence. These data will be used as a pretext for a reflection on the characteristics of the current demand for housing in Lisbon, with particular emphasis, firstly, in search of emerging trends in demand (such as the increasing demand for rental) and the profiles associated with them, interpreting them in light of both the current constraints of the real estate market, or of cultural and social changes driving new attitudes and housing values and, secondly, the analysis of consolidated demand housing trends that have come to constrain several urban dynamics in structuring social and urban fabric of Lisbon metropolis (such as the tendency shown by many studies to a residential mobility characterized by geographical continuity).